Value as an Ontological Problem in R. Ingarden’s Phenomenology - Sodeika, Tomas (Problemos, 1979)
Among axiological problems by R. Ingarden attention is focused on the ontology of values. His attempt to ground the objectivity of values is based on a special field of being. Thus, the remaining ontological indefiniteness, however, points to the possibility of understanding the value of being as a product of constitutive activities of the transcendental subject.